Striatal responsiveness to reward under threat‐of‐shock and working memory load: A preliminary study. Issue 10 (26th September 2019) - Gaillard, Claudie; Guillod, Matthias; Ernst, Monique; Torrisi, Salvatore; Federspiel, Andrea; Schoebi, Dominik; Recabarren, Romina E.; Ouyang, Xinyi; Mueller‐Pfeiffer, Christoph; Horsch, Antje; Homan, Philipp; Wiest, Roland; et al.
Abstract: Introduction: Reward and stress are important determinants of motivated behaviors. Striatal regions play a crucial role in both motivation and hedonic processes. So far, little is known on how cognitive effort interacts with stress to modulate reward processes. This study examines how cognitive effort (load) interacts with an unpredictable acute stressor (threat‐of‐shock) to modulate motivational and hedonic processes in healthy adults. Materials and Methods: A reward task, involving stress with unpredictable mild electric shocks, was conducted in 23 healthy adults aged 20–37 (mean age: 24.7 ± 0.9; 14 females) during functional magnetic resonance imaging (fMRI). Manipulation included the use of (a) monetary reward for reinforcement, (b) threat‐of‐shock as the stressor, and (c) a spatial working memory task with two levels of difficulty (low and high load) for cognitive load. Reward‐related activation was investigated in a priori three regions of interest, the nucleus accumbens (NAcc), caudate nucleus, and putamen. Results: During anticipation, threat‐of‐shock or cognitive load did not affect striatal responsiveness to reward. Anticipated reward increased activation in the ventral and dorsal striatum. During feedback delivery, both threat‐of‐shock and cognitive effort modulated striatal activation. Higher working memory load blunted NAcc responsiveness to reward delivery, while stress strengthened caudate nucleus reactivity regardless reinforcement or load. Conclusions: These findings provide initial evidence that both stress and cognitive load modulate striatal responsiveness during feedback delivery but not during anticipation in healthy adults. Of clinical importance, sustained stress exposure might go along with dysregulated arousal, increasing therefore the risk for the development of maladaptive incentive‐triggered motivation. This study brings new insight that might help to build a framework to understand common stress‐related disorders, given that these psychiatric disorders involve disturbances of the reward system, cognitive deficits, and abnormal stress reactivity. Abstract : Reward and stress are important determinants of motivated behaviors. Of clinical significance, a major challenge is to understand under which circumstances motivated behaviors might get disrupted. This study examines how cognitive effort interacts with an unpredictable acute stress exposure (threat‐of‐shock) to modulate motivational and hedonic processes in healthy adults. Our results provide initial evidence that both stress and cognitive load modulate striatal responsiveness during feedback delivery but not during anticipation in healthy adults. This study brings new insight that might help to build a framework to understand common stress‐related disorders, given that these psychiatric disorders involve disturbances of the reward system, cognitive deficits, and abnormal stress reactivity.